2012
DOI: 10.1177/0148607112444608
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Computerized Prescribing and Calculating System on Hypo‐ and Hyperglycemias and on Prescribing Time Efficiency in Neonatal Intensive Care Patients

Abstract: CPOE including a special CDS tool preserved accuracy for calculation and control of glucose intake and increased prescribing time efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…44 Notably, Maat and colleagues identified no reduction in medication errors associated with their implementation of CDS to assist in managing hypo/hyperglycaemia, but they did observe reductions in time taken to perform simple (1.3; 0.3-2.3 min) or complex orders (8.6; 5.1-12.1 min). 49 The potential for altered intervention effectiveness due to local variable factors is raised by Abboud and colleagues, who identified no reduction in gentamicin monitoring errors following the introduction of CDS as part of the prescribing process. 41 In this case, the authors suggested that the intervention had minimal benefit because they already had a clinical pharmacist responsible for ensuring monitoring was performed correctly, but results could differ in settings where clinical pharmacists are not present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Notably, Maat and colleagues identified no reduction in medication errors associated with their implementation of CDS to assist in managing hypo/hyperglycaemia, but they did observe reductions in time taken to perform simple (1.3; 0.3-2.3 min) or complex orders (8.6; 5.1-12.1 min). 49 The potential for altered intervention effectiveness due to local variable factors is raised by Abboud and colleagues, who identified no reduction in gentamicin monitoring errors following the introduction of CDS as part of the prescribing process. 41 In this case, the authors suggested that the intervention had minimal benefit because they already had a clinical pharmacist responsible for ensuring monitoring was performed correctly, but results could differ in settings where clinical pharmacists are not present.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic medication prescribing and atuomated dose checking [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Computerized physician order entry (n = 5)…”
Section: Intervention Type Example Of Intervention Referencesmentioning
confidence: 99%
“…Dutch clinical pharmacy focuses on individual patient treatment—for instance, by developing automated CDS and rules tailored to specific patients 19 20…”
Section: Introductionmentioning
confidence: 99%
“…However, there are studies indicating positive effects of CPOE systems. For example, in a study by Maat et al, the findings indicated a positive impact of the CPOE system on saving time when prescribing (30). Similarly, Balina et al and Hoonakker et al also showed that the use of CPOE systems led to saving prescription time (14, 2).…”
Section: Discussionmentioning
confidence: 99%